Analysis of data with spatial structure in wireless communication systems - TIAN Nai-shuo1; LIU Ming-xing2; MA Zhan-you1 (Tongxin xuebao)
By introduced spatial queues theory,a SPHAP/M/c/c loss system was brought forward to model the admit process of traffic form different service area,using spatial phase type arrival process describe the spatial structure of the traffic from different sectors in the same zone.The exact spatial performance measure such as channel utilization ratio of the system and the sectors,blocking probability of the system and the sectors is got.And these can be used to analysis and design the spatial structure of the system.A strategy is designed to optimize the system,and via system simulation is got the optimization results.